2001
DOI: 10.2174/1386207013331057
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Combinatorial Pooled Libraries Using Mass Spectrometry

Abstract: Parallel synthesis techniques aim to prepare collections of single compounds which, once tested, can easily be identified by their sole location in the synthesic array. On the other hand, true combinatorial chemistry produces libraries of compounds as mixtures of variable size which require a deconvolution procedure for identification of the active hits or leads. In the latter case, analytical methods are crucial for the success of the strategy and mass spectrometry plays a major role. If the goal is to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Our efforts toward obtaining a universal quantitative detection regime have been focused upon the evaporative light-scattering detector (ELSD) and the chemiluminescent nitrogen detector (CLND). Both of these detectors have been used for a number of years to aid quantification and purity assessment in conjunction with high-throughput chemistry programs. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our efforts toward obtaining a universal quantitative detection regime have been focused upon the evaporative light-scattering detector (ELSD) and the chemiluminescent nitrogen detector (CLND). Both of these detectors have been used for a number of years to aid quantification and purity assessment in conjunction with high-throughput chemistry programs. …”
mentioning
confidence: 99%
“…Taylor et al found the absolute error for a set of chemically and structurally diverse compounds averaged approximately ±10%. Shah et al used flow injection analysis (FIA) in conjunction with CLND and MS to analyze up to 1000 compounds per day.…”
mentioning
confidence: 99%
“…Mass analyzers of the single and triple-stage types have played roles in the quantitative study of drug metabolism 69 and endogenous biologically active substances [72][73][74] and in the qualitative study of combinatorial chemistry. [146][147][148][149] These mass analyzers coupled with ESI, APCI and TSP are favorable for combinations with liquid separation techniques, such as HPLC and capillary electrophoresis (CE).…”
Section: ·1 Quadrupole Mass Spectrometermentioning
confidence: 99%
“…Another important factor which impacts the quality of the results from any HTS assay is the collection or library of compounds. The quality of the compound collection screened is paramount and has been discussed in many published reports. From an analytical perspective, the purity of a compound collection is now being addressed by many laboratories, typically by MS-based methods either for the characterization or purification of compounds. In our laboratories, all of the library compounds are purified using LC/MS, where fractionation is based on the molecular ion of the target compound. , Compounds are then controlled for identity and quantitated in their respective DMSO stock solutions by flow injection analysis (FIA) MS/UV/chemiluminescent nitrogen detection (CLND)/evaporative light scattering detection (ELSD).…”
mentioning
confidence: 99%